Preimplantation genetic testing for aneuploidy: A review of published blastocyst reanalysis concordance data. (4th October 2020) - Marin, Diego; Xu, Jia; Treff, Nathan R.
Abstract: Preimplantation genetic testing for aneuploidy (PGT‐A) reduces miscarriage risk, increases the success of IVF, shortens time to pregnancy, and reduces multiple gestation rates without compromising outcomes. The progression of PGT‐A has included common application of next‐generation sequencing (NGS) from single nucleotide polymorphism microarray, quantitative real‐time PCR, and array comparative hybridization platforms of analysis. Additional putative advances in PGT‐A capability include classifying embryos as mosaic and predicting the presence of segmental imbalance. A critical component in the process of technical validation of these advancements involves evaluation of concordance between reanalysis results and initial testing results. While many independent studies have investigated the concordance of results obtained from the remaining embryo with the original PGT‐A diagnosis, compilation and systematic analysis of published data has not been performed. Here, we review results from 26 primary research articles describing concordance in 1271 human blastocysts from 2260 pairwise comparisons. Results illustrate significantly higher discordance from PGT‐A methods which utilize NGS and include prediction of mosaicism or segmental imbalance. These results suggest caution when considering new iterations PGT‐A.